Denjong Sunglu - (:unkn) unknown (Denzong Lhomen Kiduk (Sikkim Culture and Heritage Foundation), 2009)
This is the collection of bhutia language folk songs. Folk songs are identity of any society. In this book bhutia society and their culture traditions are described by folk songs.
Keywords: Bhutia; Folk Literature; Bhutia; Bhutia